The usefulness of calculating the dispersion of QT and QTC intervals in athlethes adolescents - Dimitriu, D.A.G.; Dimitriu, L. (Archives of cardiovascular diseases, 2024)
Highlighting the increase in dispersion of QT and QTc intervals can be a useful indicator for the risk of ventricular arrhythmias in young athletes. Evaluation of the dispersion of QT and QTc intervals in adolescent athletes to assess the type of physical effort wich can performed. Subjects: 51 athletic teenagers (14–17 years old) divided into 2 groups: group I: 25 athletes trained for endurance sports (runners, soccer players); group II: 26 athletes trained for strength sports (fighters, boxers). Control group: 20 teenagers of the same age group, without any sign of cardiac distress. ECGs were evaluated in all adolescents, athletes and non-athletes: in three consecutive cardiac ECG cycles, the QT interval dispersion (QTD) (the difference between the maximum and minimum value of the QT interval) and the QTc interval dispersion (QTcD) were calculated (Bazzet's formula). The mean values of QTD and QTcD in groups I and II were higher than those in the control group, but the difference is not statistically significant. Lot I: QTD: 43.54±21.03 msec; QTcD: 50.81±19.34 msec; Lot II: QTD: 48.23±12.56 msec; QTcD: 53.59±17.21 msec; Control lot=QTD: 35.88±10.22 msec; QTcD: 39.23±14.81 msec. The highest values of QT interval dispersion were found in adolescent strength-trained athletes. The highest values of QTD and QTcD dispersion were found in adolescent athletes in the second group, which may be at a higher risk of ventricular arrhythmia. There was no case with a longer than normal QT interval value. Along with other ECG parameters, it is useful to research the screening of the QT interval and the dispersion of the QTc interval during periodic and especially pre-competitive controls, as an indicator of the risk of severe ventricular arrhythmias in adolescents athletes.